An Exploration of Using Form Generation to Expand Creative Ideas and Imagination Based on the Context of Form Generation and Creative Thinking - Tan, Xiujiang; Tan, Long (Transactions on Social Science, Education and Humanities Research, 2023)
Form generation is a technique that helps to expand creative ideas and imagination by changing the form, structure or constraints of a creation to stimulate new ideas. Experiment with different media, such as pen and paper, digital tools, sound recordings, etc., in order to change the creative environment. Use different types of canvas, paper or virtual spaces to allow for experimentation with different creative expressions. Setting time limits, such as 15 minutes to complete a painting, poem, or short story, to force rapid creative generation. Limit the colours, number of words or materials used, which can stimulate creativity. Use constraining writing techniques, such as using words that begin with a specific letter, following a specific rhyming pattern, or a word count limit, which can help to challenge yourself and create a unique piece of work. Experiment with different narrative structures such as non-linear narratives, flashback stories, and multi-line stories to add variety and depth to creative writing. Use a random generator or lottery to choose words, plot elements or character traits, which can generate unexpected ideas. Choose a piece of work that already exists, mimic its form or structure, and then try to innovate and improve it to make it more interesting or personalised. Think about a topic or concept from different perspectives, e.g. science, history, philosophy, etc. for diverse inspiration. Blend knowledge from different fields, e.g. combining music and painting, or combining scientific concepts with literary elements, to create novel works. Look closely at the details of everyday life and listen to the voices and stories around you, which can be a source of creative inspiration. Set up an environment that focuses on creativity, such as an art studio, a writing corner, or a music composition room, to stimulate creativity. By utilising form-generating methods, it is possible to break out of conventional thinking patterns, stimulate creativity, discover new creative ideas and expand the imagination in different fields. These techniques contribute to more innovation and achievement in the fields of art, literature, music and science.